Hip myodysplasia: treatment - Castiglioni, Néstor; Maquieira, Carlos; Pérez Álvarez, Manuel (Cirugía del Uruguay, 1973)
Success of treatment depends on early diagnosis. Treatment is based on the etiogenic concept of this disease which Prof. Bado blames on the muscle. Genetic and hereditary muscular dysplasia affects certain muscular groups -above all psoas and adductors- and through growth, determines cervical and epyphiseal alterations and secondary alterations of cotyloid cavity (acetabulum) which, in turn, lead to spontaneous thigh displacement. Disease is evolutive and may appear at different periods of the child's life, in ny stage of evolution. Consequently, we find a diversity of anatomoclinical situations that cannot be solved by one single therapeutic formula. Ideally, the patient should be treated during the very early stages. The thigh should be adjusted and positioned correctly, maintaining it so during all the time necessary. Before the age_ of three months, surgery is not generally required; a splint, or plaster cast, followed by a splint, is all that is required. Between the. ages of 3 to 6 onths, we find two types of situations: Easy adjustment and positioning: non-surgical treatment; plaster cast or splint adjustment: surgical treatment, abscission of adductors and psoas and, if so required, capsule, followed by plasetr cast and/or splint. After the age_ of 6 months, treatment is generally surgical followed by plaster cast and/or splint. After the age of one year, adjustment is surgical and is followed, one month later, by derotating varus osteotomy. Walking is allowed 2 months after osteotomy.